2021
DOI: 10.1590/s0004-2803.202100000-91
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Biliary Cannulation: Should We Always Try a Second Ercp After a Failed Needle-Knife Fistulotomy?

Abstract: BACKGROUND: A successful bile duct cannulation is a prerequisite for the realization of endoscopic retrograde cholangiopancreatography (ERCP). When biliary cannulation is not possible, needle-knife fistulotomy (NKF) can be performed. However, when biliary access is not successfully achieved even after performing NKF, it is possible to interrupt the procedure, and repeat the ERCP after a short interval. OBJECTIVE: The aim of this study is to analyze if repeating an ERCP after a short interval of 48 hours is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that experienced endoscopists using a needle-knife have improved the cannulation success rate to between 85% and 99%; however, the matter of selecting the best substitute among the available options in the event of initial ERCP failure still holds interest [1,11]. A subsequent ERCP within a few days is an effective and safe therapy for patients who are clinically stable, with a success rate of 68%-79% [2,12,13]. The results of the current study reveal an overall success rate of 76.6%, which supports the validity and vitality of a second ERCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that experienced endoscopists using a needle-knife have improved the cannulation success rate to between 85% and 99%; however, the matter of selecting the best substitute among the available options in the event of initial ERCP failure still holds interest [1,11]. A subsequent ERCP within a few days is an effective and safe therapy for patients who are clinically stable, with a success rate of 68%-79% [2,12,13]. The results of the current study reveal an overall success rate of 76.6%, which supports the validity and vitality of a second ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP) is a minimally invasive intervention that has established itself as the gold standard therapeutic option for various pancreaticobiliary conditions [1]. Nonetheless, there are times when ERCP is ineffective, even when performed by highly trained professionals or at major healthcare institutions [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to Flumignan [ 18 ] and Deng [ 19 ], a second fistulotomy attempt is feasible, and safe, and can be attempted after a short 48-hour interval if the first ERCP attempt is unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Methods This was a cross-sectional study, with retrospective data collection from 2233 ERCP exams with 528 EFP procedures, conducted from November 2006 to August 2022 analysis of results regarding cannulation success and complications. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19…”
mentioning
confidence: 99%